Identification of the Potential Key Circular RNAs in Elderly Patients With Postoperative Cognitive Dysfunction - Gao, Rui; Chen, Chan; Zhao, Qi; Li, Ming; Wang, Qiao; Zhou, Lu; Chen, Erya; Chen, Hai; Zhang, Yue; Cai, Xingwei; Liu, Changliang; Cheng, Xu; et al. (Frontiers in Aging Neuroscience, 2020)
Background Postoperative cognitive dysfunction (POCD) is one of the severe complications after surgery, inducing low life quality and high mortality, especially in elderly patients. However, the underlying molecular mechanism of POCD remains largely unknown, and the ideal biomarker for clinical diagnosis and prognosis is lacking. Circular RNAs (circRNAs), as a unique class of non-coding RNAs, were characterized by its stability and conservativeness, serving as novel biomarkers in various diseases. Nevertheless, the role of circRNAs in the occurrence of POCD remains elusive. Methods To investigate the differentially expressed circRNAs in the serum of POCD patients and its potential role in the development of POCD, we performed a circRNA microarray to screen the differentially expressed circRNAs in the serum samples from three patients of the POCD group and three paired patients of the non-POCD group. Subsequently, quantitative real-time polymerase chain reaction analysis (qRT-PCR) was utilized to verify the microarray data with the serum samples from 10 paired patients. Cytoscape software was used to construct the circRNA–miRNA–mRNA network for circRNAs with different expression levels as well as the target genes. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analyses showed the biological functions of the differentially expressed circRNAs target genes. Results In total, we have analyzed 10,198 circRNAs through the microarray. Compared with the non-POCD patient group, there were 210 differentially expressed circRNAs with 133 upregulated and 77 downregulated in the POCD group (≥2-fold differential expression, P ≤ 0.05). The qRT-PCR confirmed 10 circRNAs with different expressed levels, and the results were consistent with the microarray findings. Among them, hsa_circRNA_001145, hsa_circRNA_101138, and hsa_circRNA_061570 had the highest magnitude of change. The GO analysis showed that the differentially expressed circRNAs were associated with the regulation of the developmental process, cell-to-cell adhesion, and nervous system development. The KEGG analysis showed that the target genes of circRNAs were enriched in the MAPK signaling pathway and RAS signaling pathway. According to the targetscan7.1 and mirdbV5 databases, the circRNA–miRNA–mRNA network was constructed, and these results provided a vital landscape of circRNA expression profile in POCD. Conclusions Our study provides an essential perspective for the differential expression of circRNAs in POCD patients. Further studies need to be performed to explore their potential therapeutic roles in the development of POCD.